Monitoring breastfeeding indicators in high‐income countries: Levels, trends and challenges - Juliana S. Vaz; Maria Fatima S. Maia; Paulo A. R. Neves; Thiago M. Santos; Luís Paulo Vidaletti; Cesar Victora (Wiley, 2021)
Abstract Monitoring indicators of breastfeeding practices is important to protect and evaluate the progress of breastfeeding promotion efforts. However, high‐income countries lack standardized methodology to monitor their indicators. We aimed to update and summarize nationally representative annual estimates of breastfeeding indicators in high‐income countries and to describe methodological issues pertaining to the data sources used. A review was conducted through population‐based surveys with nationally representative samples or health reports from nationally representative administrative data of electronic surveys or medical records. Methodological aspects and rates of all breastfeeding indicators available were summarized by country. The median and annual growth of breastfeeding in percentage points within countries with time‐series data were estimated. Data from 51 out of 82 high‐income countries were identified. The data were obtained through surveys (n = 32) or administrative data (n = 19). Seventy‐one percent of countries have updated their indicators since 2015. Ever breastfed was the indicator most frequently reported (n = 46), with a median of 91%. By 6 months of age, the median equals 18% for exclusive and 45% for any breastfeeding. At 12 months, the median of continued breastfeeding decreased to 29%. The annual growth rate for ever breastfed, exclusive and any breastfeeding at 6 months and continued at 12 months varied from 1.5 to −2.0, 3.5 to −3.1, 5.0 to −1.0 and 5.0 to −1.9, respectively, with positive changes for most countries. Stronger interventions are needed to promote breastfeeding in high‐income countries as a whole, and investments are required to monitor trends with standardized methodologies.